Do all material incentives for prosocial activities backfire? The response to cash and non-cash incentives for blood donations - Nicola Lacetera; Mario Macis (Institute for the Study of Labor (IZA), 2009)
Experimental studies document that financial rewards discourage the performance of altruistic activities, because they destroy intrinsic altruistic motivations. We set up a randomized-controlled experiment, through a survey administered to 467 blood donors in an Italian town, and find that donors are not reluctant to receive compensation in general: A substantial share of respondents declared they would stop being donors if paid a small amount of cash, but we do not find such effects when a voucher of the same nominal value is offered instead. The aversion to direct cash payments is particularly marked among women and older respondents, while there are neither gender nor age differences in the response to the voucher. Implications for research and public policy are discussed.
urn:nbn:de:101:1-200910141369
Keywords: D12; D64; I18; 330; Incentives; altruism; public good provision; pro-social behavior; public health; Blutspende; Altruismus; Ökonomischer Anreiz; Couponing; Soziales Verhalten; Test; Italien